2007
DOI: 10.1016/j.neuropharm.2007.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparing analgesia and μ-opioid receptor internalization produced by intrathecal enkephalin: Requirement for peptidase inhibition

Abstract: Opioid receptors in the spinal cord produce strong analgesia, but the mechanisms controlling their activation by endogenous opioids remain unclear. We have previously shown in spinal cord slices that peptidases preclude mu-opioid receptor (MOR) internalization by opioids. Our present goals were to investigate whether enkephalin-induced analgesia is also precluded by peptidases, and whether it is mediated by MORs or delta-opioid receptors (DORs). Tail-flick analgesia and MOR internalization were measured in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 64 publications
(117 reference statements)
1
37
0
Order By: Relevance
“…In them the percentage of MOR neurons with internalization in lumbar spinal segments was negligible: L1, 0.4±0.4 %; L2, 1.8±1.1 %; L3, 1.0±0.5 %; L4, 2.3±1.8 %; L5, 3.5±2.2 %; L6, 1.5±1.5 % (n=3 rats). We have previously shown that peptidase inhibitors by themselves do not produce MOR internalization (Chen et al, 2007). In other experiments we also measured the internalization of NK1Rs in lamina I neurons in order to assess the intensity of the noxious stimuli.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In them the percentage of MOR neurons with internalization in lumbar spinal segments was negligible: L1, 0.4±0.4 %; L2, 1.8±1.1 %; L3, 1.0±0.5 %; L4, 2.3±1.8 %; L5, 3.5±2.2 %; L6, 1.5±1.5 % (n=3 rats). We have previously shown that peptidase inhibitors by themselves do not produce MOR internalization (Chen et al, 2007). In other experiments we also measured the internalization of NK1Rs in lamina I neurons in order to assess the intensity of the noxious stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the inability of opioids to produce MOR internalization in the absence of peptidase inhibitors does reflect their inability to activate them. Thus, intrathecal Leu-enkephalin failed to produce analgesia in the tail-flick test, even at high doses (100 nmol), but it produced analgesia at low very doses (0.3 nmol) when it was co-injected with peptidase inhibitors (Chen et al, 2007). Another study (Kishioka et al, 1994) found that peptidase inhibitors substantially increased the analgesia produced by Metenkephalin, dynorphin or electroacupuncture.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Spinal cord sections were labeled for MORs as described previously (Song and Marvizó n, 2003b;Chen et al, 2007;Chen et al, 2008;Chen and Marvizó n, 2009). Rats were killed with pentobarbital (100 mg/ kg) and fixed immediately by aortic perfusion of 100 ml phosphate buffer (0.1 M sodium phosphate, pH 7.4) containing 0.01% heparin, followed by 400 ml of ice-cold fixative (4% paraformaldehyde, 0.18% picric acid in phosphate buffer).…”
Section: Methodsmentioning
confidence: 99%
“…1A) suggests that receptors other that MORs contribute to the suppression of hyperalgesia during the remissionphaseoflatentsensitization.Descendingnoradrenergicpathwaysproduceanalgesia by acting on ␣ 2 receptors in the dorsal horn (Yaksh, 1985;Pertovaara, 2006), which are mainly ␣ 2A Rs located in primary afferent terminals (Stone et al, 1998;Chen et al, 2008). Therefore, we hypothesized that ␣ 2A Rs contribute to suppressing hyperalgesia in latent sensitization and predicted that an ␣ 2A R antagonist would produce reinstatement during the remission phase.…”
Section: Mor Constitutive Activity In Latent Sensitization: Effects Omentioning
confidence: 98%